RESILIENSI IBU TUNGGAL: PERAN KEBERSYUKURAN DAN REGULASI EMOSI: Becoming a Resilient Single Mother: Role of Gratitude and Emotion Regulation - Lidiawati, Krishervina Rani; Dewi, Wiwit Puspitasari; Simamora, Shema Christy Noya (Jurnal Ilmu Keluarga dan Konsumen, 2024)
The death of a spouse is a deep sorrow for a single mother. In addition to causing grief, there is also a new challenge faced by single mothers, namely the challenge of carrying out multiple roles. This dual role is not easy for single mothers to live alone. In difficult times, single mothers are more susceptible to stress and tend to bring up negative emotions more easily. As a single parent, it is important for single mothers to have a resilient ability to go through these challenges and difficulties. This study aims to explore the resilience of single mothers by involving the role of emotion regulation and gratitude. Quantitative research methods were used in this study with the Emotion Regulation Questionnaire, Gratitude Questionnaire, and Connor Davidson Resilience Scale 25 as measurement instruments. Results showed that gratitude and emotion regulation simultaneously predicted single maternal resilience by 23,6%. Gratitude and emotional regulation support single mothers to elicit positive responses to conditions, especially difficult conditions, thus helping single mothers become resilient. This finding means that single mothers are important for single mothers to apply emotional regulation and gratitude in life so that single mothers are able to survive or rise from difficult times.